Cover Picture: Chainmail Catalyst of Fe3O4@C/CNTO‐Modified Celgard Separator with Low Metal Loading for High‐Performance Lithium–Sulfur Batteries (13/2020). Issue 13 (1st April 2020) - Du, Jingguang; Ahmed, Waqas; Xu, Jie; Zhang, Mingyuan; Zhang, Zhiliang; Zhang, Xinsheng; Niu, Dongfang
Abstract : The cover picture shows that the chainmail catalyst of Fe3 O4 @C/CNTO (CNTO=oxidized carbon nanotubes) with low metal loading was innovatively constructed and applied into the coating layer of a Celgard separator for Li‐S battery. Fe3 O4 serves as the active site to promote the interconversion of lithium polysulfides; the carbon‐shell‐encapsulated Fe3 O4 leads to an integrated 3D architecture with the CNTO support to provide a continuous pathway for facile electron transport. Benefiting from the catalytic and conductive composite interface, the battery with the Fe3 O4 @C/CNTO‐modified separator delivers a satisfactory specific capacity and excellent stability. Cover picture designed by Dongfang Niu. More information can be found in the Full Paper by Dongfang Niu et al. (DOI: 10.1002/slct.202000366 )